Effectiveness of chitosan nanoparticles, and novel chemical irrigants with surfactant on smear layer removal and microhardness alteration - Monika Khangwal; Ravinder Solanki; Hena Rahman; vinay; Neha Saini; Nilesh Bagde (Journal of Oral Biology and Craniofacial Research)
Objective: This current study was designed to compare and correlate between smear layer eradication and reduction in microhardness by natural 0.2%chitosan nanoparticles and novel chemical irrigants with surfactant at the apical root third. Materials and method: One hundred and twenty straight single-rooted extracted lower premolars were decoronated and working length obtained with #10 K-file. Pro-taper rotary files were used till apical size F3. The canals were simultaneously flushed with assigned irrigant containing surfactant [(ChX-Ultra, NaOCl-Extra, Pro-EDTA, 0.2%chitosan nanoparticles, Biopure MTAD]. The samples were randomly divided into two equal groups (n = 60). InGroup S (n = 60), the residual smear layer was examined by scanning electron microscope and in Group M(n = 60) microhardness was determined by Vickers Microhardness Tester. Further both groups were divided into six equal groups (n = 10 each) according to assigned irrigating solutions.For smear layer removal; Kruskal-Wallis tests followed by pair wise comparison using Mann Whitney U test was done. For change in microhardness ANOVA and post hoc Tukey tests was done. Results: Maximum smear layer removal was recorded in Biopure MTAD (1.8 ± 0.63), followed by pro-EDTA (2.2 0 ± 0.63) then 0.2%chitosan (2.6 ± 0.51), then NaOCL Extra (3.5 ± 0.53)and least in CHX-Ultra (4.4 ± 0.52) and saline (5.0 ± 0.00). Pro-EDTA group (12.8 ± 2.47) revealed significant highest reduction in microhardness followed by Biopure MTAD (8.01 ± 3.06), 0.2%chitosan nanoparticles (5.48 ± 2.87), NaOCl-Extra (5.44 ± 1.62) and least recorded in CHX-Ultra (4.94 ± 1.43) and saline (3.04 ± 0.63). Conclusion: The elimination of the smear layer is always accompanied by a reduction in microhardness. Moreover, irrigant with surfactant and chelators enhanced smear layer removal, with best perceived in Biopure MTAD.